2022
DOI: 10.1002/lrh2.10354
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Cystic Fibrosis Learning Network: Interventions to promote collaboration and data‐driven improvement at scale

Abstract: Introduction: A learning health network is a type of learning health system in which stakeholders use network organization to improve health and health care. Building on existing resources in the cystic fibrosis (CF) community, the Cystic Fibrosis Learning Network (CFLN) was designed to improve medical outcomes and quality of life through an intentional focus on achieving reliable evidence-based chronic care delivery and creating a system for data-driven collaborative learning. Methods:We describe the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Interview respondents reported that the triad leadership structure 22 (physician leaders, QILs, and PFPs) supports governance and guides decision‐making and prioritization of local and network level activities. They stated that this integrated leadership structure models that seen with coproduction 33‐35 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interview respondents reported that the triad leadership structure 22 (physician leaders, QILs, and PFPs) supports governance and guides decision‐making and prioritization of local and network level activities. They stated that this integrated leadership structure models that seen with coproduction 33‐35 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, our evaluation does not include objective measures of impact. Changes associated with specific CFLN initiatives are reported elsewhere (eg, telehealth) 22,30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CFLN is a network of accredited CF programs 14 that practice continuous quality improvement. 15 The CFLN at the time of recruitment had 26 of a total 39 programs who had pediatric-…”
Section: Bmentioning
confidence: 99%
“…This collaborative project with PwCF and parent and family partners (PFP) has worked to change our practice by increasing our use of previsit planning and patient centered agenda setting. The Cystic Fibrosis Learning Network has increased parent and family partners participation with almost all Cystic Fibrosis Learning Network participating centers having them with 74% of PFP actively participating in quality improvement initiatives [82].…”
Section: Coproductionmentioning
confidence: 99%